Slope Stability Analysis Based on Type, Physical And Mechanical Properties Rock in Teluk Pandan District, East Kutai Regency, East Kalimantan - Sujiman Kusnadi (UIR PRESS, 2017)
Research was located In Teluk Pandan District, East Kutai Regency, East Kalimantan Province. It’s aimed to determine the lithology in the research area and to find out how the amount of slope that will be a landslide at that location. The research conducted with the analysis of coring drilling results and then analyzed in the laboratory of rock mechanics to get the characteristic of physical and mechanical properties of the rocks. The data analysis using Hoek and Bray Method. The results showed that in the area study has a sedimentary rock lithology fine to medium detritus, such as claystone, siltstone and sandstone, as well as inserts are coal and shale. Based on the results of laboratory analysis of rock mechanics obtained density between 2,648 to 2,770. While the test results obtained value triaxial cohesion between (6.66 - 9:05) Kg / cm2, friction angle in between (37.19 - 44.08)o, cohesion residual (2.72 - 3.10) Kg / cm2, residual friction angle (27.22 - 32.44)o. While the direct shear test the cohesion of the summit between (6.66 - 9:05) Kg / cm2, friction angle in the cohesion peak (36.15 - 43.00)o, cohesion residual (2:22 to 3:10) Kg / cm2, friction angle in the cohesion residual (37.22 - 33.85)o. The simulation results stability of the slope stability Hoek and Bray using rockslide software, the result is that if the slope with a single slope stability, the stability of the slope is 60o, and if the slope with the stability of the slope overall stability of the slope is 48o.